Climate Change, Torn Between Myth and Fact. - Cranganu, Constantin (Cambridge Scholars Publisher, 2021)
This book is both a plea and an invitation to consider climate change from a multi-faceted perspective, taking into account (geo)physical, social, cultural, psychological, religious, mythological, economic, and judicial viewpoints, among others. As such, it will serve as a useful and necessary guide towards a better understanding of our own mental structures and systems of preferences, ideologies, or beliefs.